COMPARATIVE ANALYSIS OF PROBING AND CONTRAST RADIOGRAPHY FOR GENDER DETERMINATION IN RETICULATED PYTHONS (Malayopython reticulatus) - Zhi Yien Tan; Okti Nadia Poetri; Mokhamad Fakhrul Ulum (BIOTROPIA, 2024)
Article Highlights- Accurate gender identification supports effective breeding programs and ensures snakes' welfare.- This study emphasizes that probing is more reliable and efficient than contrast radiography for gender determination in reticulated pythons.- The probing method proved to have 100% accuracy in determining the gender of reticulated pythons, outperforming contrast radiography, which only achieved 75% accuracy. AbstractReticulated pythons, like most snakes, do not exhibit noticeable sexual differences, which makes gender determination necessary. Probing and contrast radiography were chosen as methods to determine sex and to compare their accuracy. Six reticulated pythons with body lengths of 128-167 cm, tail lengths of 5.4-9.6 cm, and body diameters of 1.4-3.4 cm were examined twice by probing and contrast radiography. The results showed that probing had 100% accuracy, with probe lengths ranging from 1.37-3.60 cm for male snakes and 0.3-0.76 cm for female snakes. Contrast radiography had 75% accuracy, with the hemipenis appearing as a white silhouette and female snakes appearing colorless. The accuracy rates highlight the effectiveness of probing over contrast radiography for reliable gender determination in reticulated pythons